Die Afrikaanse evangeliese gesang: 'n literêre ondersoek - Gaum, Frederik Malherbe (University of the Free State, 1969)
Abstract not available
Thesis (Ph.D. (Afrikaans and Dutch))--University of the Free State, 1969
Keywords: Hymns, Afrikaans; Sacred songs; Church music